Interactive knowledge validation and query refinement in CBR for decision support in medicine - Ou, M.; West, Geoff; Lazarescu, Mihai; Clay, C. (Springer, 2005)
In most case-based reasoning (CBR) systems there has been little research done on validating new knowledge, specifically on how previous knowledge differs from current knowledge as a result of conceptual change. This paper proposes two methods that enable the domain expert, who is non-expert in artificial intelligence (AI), to interactively supervise the knowledge validation process in a CBR system, and to enable dynamic updating of the system, to provide the best di- agnostic questions. The first method is based on formal concept analysis which involves a graphical representation and comparison of the concepts, and a summary description high- lighting the conceptual differences. We propose a dissimilarity metric for measuring the degree of variation between the previous and current concepts when a new case is added to the knowledge base. The second method involves determining unexpected classification-based association rules to form critical questions as the knowledge base gets updated.